2019
DOI: 10.1177/0300060519866270
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilis sacral spondylodiscitis and epidural abscess after sacrocolpopexy: a case report and literature review

Abstract: Spondylodiscitis with or without epidural abscess is a rare, although serious, complication after sacrocolpopexy. We present a case of an 81-year-old patient who developed anaerobic Bacteroides fragilis sacral spondylodiscitis with epidural abscess 18 weeks after laparoscopic sacrocolpopexy. Because of the patient’s old age, comorbidities, and further complications during hospitalization, she was treated conservatively with an early switch to oral antimicrobial therapy with good oral bioavailability. Because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Data extraction from PubMed provided a total of 36 abstracts, and further reference search yielded additional 8 articles, gathering a total of 52 cases, 6 7 8 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 including ours. The summary of the results is presented in Tables 1 and 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Data extraction from PubMed provided a total of 36 abstracts, and further reference search yielded additional 8 articles, gathering a total of 52 cases, 6 7 8 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 including ours. The summary of the results is presented in Tables 1 and 2 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of the literature revealed that the types of antibiotics prescribed to medically treated patients varied and might range from 4 weeks to 6 months [22]. These antibiotics included vancomycin, advanced generation cephalosporins, and clindamycin [22][23][24]. Spondylodiscitis cases can occur either with positive or negative culture test [22,25,26].…”
Section: Antibiotic Treatment During Spondylodiscitismentioning
confidence: 99%